Beyond the Core Suture: A New Approach to Tendon Repair. Issue 12 (December 2020) - Zeng, Weifeng; Albano, Nicholas J.; Sanchez, Ruston J.; Mccabe, Ronald; Vanderby, Ray; Poore, Samuel O.; Dingle, Aaron M.
Abstract : Background: Despite significant improvements in zone II flexor tendon repair over the last 2 decades, function-limiting complications persist. This article describes 2 novel repair techniques utilizing flexor digitorum superficialis (FDS) autografts to buttress the flexor digitorum profundus (FDP) repair site without the use of core sutures. The hypothesis being that the reclaimed FDS tendon autograft will redistribute tensile forces away from the FDP repair site, increasing overall strength and resistance to gapping in Zone II flexor tendon injuries compared with the current clinical techniques. Methods: Two novel FDP repair methods utilizing portions of FDS have been described: (1) asymmetric repair (AR), and (2) circumferential repair. Ultimate tensile strength and cyclical testing were used to compare novel techniques to current clinical standard repairs: 2-strand (2-St), 4-strand (4-St), and 6-strand (6-St) methods. All repairs were performed in cadaveric sheep tendons (n = 10/group), by a single surgeon. Results: AR and circumferential repair techniques demonstrated comparable ultimate tensile strength to 6-St repairs, with all 3 of these techniques able to tolerate significantly stronger loads than the 2-St and 4-St repairs ( P < 0.0001). Cyclical testing demonstrated that AR and circumferential repair were able to withstand a significantly higher total cumulative force ( P < 0.001 and P = 0.0064, respectively) than the 6-St, while only AR tolerated a significantly greater force to 2-mm gap formation ( P = 0.042) than the 6-St repair. Conclusion: Incorporating FDS as an autologous graft for FDP repair provides at least a comparable ultimate tensile strength and a significantly greater cumulative force to failure and 2-mm gap formation than a traditional 6-St repair.